GENDER EMPOWERMENT STRATEGIES IN EFFORTS FOR GENDER EQUALITY AND INCREASING FAMILY WELFARE - Aryani, Luh Ayu and I Nyoman Mahaendra Yasa (JOURNAL SCIENTIFIC OF MANDALIKA (JSM), 2021)
Gender empowerment can be realized through the level of participation of women's active roles in the economic, political and decision-making fields. Men have the assumption that men are the ones who earn the main income for the family's economic needs or that men are very dominant productive workers, but sometimes in reality this is not the case, many women are the economic bearers of the family. Empowerment of women in the economic field is one indicator of increasing welfare. When women become educated, have property rights, and are free to work outside the home and have an independent income, this is a sign of increased family welfare. Equality between men and women, refers to the equal rights, responsibilities, opportunities, treatment, and assessment for men and women in work and in the relationship between work and life. Gender equality means that all people of all ages and genders should have equal opportunities to succeed in life. Several studies suggest that the involvement of women on a micro scale plays a very important role in improving family welfare, especially avoiding the severe poverty trap. This paper is a literature review related to gender empowerment strategies in an effort to equalize gender and improve family welfare. Through literature, this paper tries to analyze gender, not only the roles and activities between men and women. This paper aims to examine gender empowerment in an effort to increase gender equality efforts, examine gender empowerment in an effort to improve family welfare and examine gender equality efforts in an effort to improve family welfare. The conclusion of this study is participation in the economy, is the work participation of women who take part in the economic sector that can provide income in the family in order to improve family welfare. Empowerment of women in the economic field is one indicator of increasing welfare. Gender equality means that all people of all ages and genders should have equal opportunities to succeed in life. By promoting gender equality in order to empower people both women and men to lift themselves out of poverty and improve living standards and well-being.